Pengaruh Temperatur Terhadap Degradasi Pigmen Tomat dalam Beberapa Jenis Minyak Nabati Komersial - Yoga Aji Handoko; Indriatmoko Indriatmoko (Jurnal Penelitian Pertanian Terapan, 2016)
The study of vegetable oils fortified with crude extract of carotenoid pigments from tomatothat contains lycopene as dominant antioxidant compounds becomes an interesting researchto be done. The aim of this research is testing the stability of the pigment of tomatoesextracts in the vegetable oil treated on some temperature levels. Spectroscopy method isused to measure the respond of pigment stability in fortified vegetables oils which treated bytemperature from 250C to 700C. Before the measurement is done by a spectrophotometerwhich connected to the thermostat, as much as 1 mg of extract pigment of tomatoes in crystalform was weighed for per sampel, then dissolved into 10 ml palm oil, coconut oil, sunflowerseed oil, and canola oil separately. The results showed that the temperature treatment causesthe value of the optical absorption decreased, which means that the pigment moleculesexperienced instability. The amount of impairment of the optical absorption withtemperature treatment from 250C to 700C at a wavelength of 482 nm, respectively, are: palmoil (Abs = 0.201); coconut oil (Abs = 0.213), sunflower oil (Abs = 0.232); and canola oil(Abs = 0.260). Decreasing value of absorbance (Abs) also indicates the lycopenedegradation that formed the derivatives molecule of this pigment.Keywords: fortification, lycopene, vegetable oil, temperature, tomato